Foreign languages for the labor market: an analysis on the role of compulsory education in Europe - Mazzacani, Danielle (Revista Internacional de Organizaciones, 2020)
It is well known that proficiency in more languages is important for labor outcomes of natives, and economic literature generally shows positive effects for those able to use multiple languages in the domestic labor market. In this context, compulsory education is likely to play a relevant role in identifying to what extent additional languages matter for the native workforce. Indeed, institutional education systems are often the main providers of individual skills in a country, including language skills, and compulsory education is reasonably unrelated to individual characteristics affecting choices of language acquisition. However, while some studies on co-official languages and labor in multilingual countries build their strategy on compulsory schooling, it seems that no study on indigenous workers considers it for foreign languages. As a first step of future analyses on foreign languages and labor in Europe, in this paper I try to analyze whether compulsory education affects foreign language proficiency of European native adults. I find that being taught foreign languages during compulsory schooling has positive effects on the probability of knowing them, ranging from 3 to 5 percent.